Remote e-learning model in the post COVID-19 era; building a resilient higher education strategy - Michael Kamoyo; Tavengwa Masamha; Lovemore Chikazhe (Cogent Education)
The research explored the pedagogic impacts of the virtual e-learning management platforms adopted at Chinhoyi University of Technology, as a COVID-19 pandemic resilience strategy. It established the link between students’ e-learning adoption patterns and e-learning performance outcomes. Structural equation modelling was applied in analysing data from a sample of 70 undergraduate students. The results indicated that despite management’s good intentions in mitigating the COVID-19 disaster on higher education, the performance of virtual e-learning system as a pandemic response strategy was curtailed by more inhibitors than accelerators. Factors such as unequal access to e-learning facilities, network connectivity challenges, internet access, unreliable electricity and unaffordability of compatible digital gadgets, constituted serious impediments to virtual e-learning adoption. Very few undergraduate students accessed the most versatile BigBlueButton e-learning platform, with very limited application of offline e-learning technologies like CD-ROM and flash disks. Instead, WhatsApp groups with the least e-learning interactive capabilities were most popular and highly subscribed. The implications are that universities’ future e-learning pandemic resilience strategies should be supported by national level interventions that promote inclusivity and accessibility to e-learning facilities. The use of offline e-learning content material recorded in videos and flash disks should be promoted as low-cost e-learning management systems.